PENERAPAN MEDIA FLASHCARD DALAM MENINGKATKAN KEMAMPUAN MEMBACA AKSARA LONTARA SISWA MIS AS’ADIYAH 66 TIMORENG KABUPATEN WAJO - Mulyasti; Martini; Aidil Sudarmono R, Muh.; M, Nurlaelah; Hasan, Salim; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to apply flashcard media and determine the results of its application in improving the reading ability of Lontara script of students of MIS As'adiyah 66 Timoreng, Wajo Regency. This research uses the classroom action research (CAR) method in two cycles with each cycle having two meetings consisting of the planning, action implementation, observation and reflection. The subjects of the study were 26 third-grade students with data collection techniques of observation, interviews, tests, and documentation. The results of the study showed an increase in the value of learning outcomes that met the KKM value from the pre-cycle with a percentage of 4.17% (average value of 39.17) to 41.67% (average value of 62.91) in cycle I, then in cycle II to 87.5% (average value of 83.33). Thus, it can be concluded that the application of flashcard media can improve the reading ability of Lontara script of class III students of MIS As'adiyah 66 Timoreng, Wajo Regency in the Bugis Regional Language subject.